MENINJAU TINDAKAN PEMERINTAH DALAM MENERAPKAN ASAS TIDAK MENYALAHGUNAKAN WEWENANG: ANALISA TERHADAP PELANGGARAN KEDISIPLINAN PNS - Nathasya Berlian; Belyana Fauza (Peneliti.net, 2023)
Abuse of authority in the Discipline of Civil Servants (PNS) is an important issue and needs to be taken seriously. Abuse of authority can undermine the principles of integrity, transparency and accountability in public services. And result in decreased work responsibility and an attitude of underestimating obligations, which makes us further away from achieving good governance. This paper aims to analyze the concept of civil servant discipline and the related phenomenon of abuse of authority.In the context of civil servant discipline, emphasis is given to the definition and implementation of civil servant discipline as a major factor for monitoring and enforcing rules within the bureaucracy. Factors affecting civil servant discipline are also analyzed, including laws and regulations governing disciplinary actions, reward and punishment systems, as well as cultural and organizational factors both from within employees and factors from outside employees that can affect the behavior of civil servants.